2015
DOI: 10.1039/c5ra08393a
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-2,6-dicarboxylic acid for the sensitization of europium(iii) luminescence with very long lifetimes

Abstract: Convenient and mild syntheses of two europium(III) complexes, Na[Eu(dipic) 2 $3H 2 O]$4H 2 O (dipic ¼ dipicolinate anions) and Na[Eu(dipic) 2 $phen]$H 2 O (phen ¼ 1,10-phenanthroline), were reported. These two europium(III) complexes were confirmed by 1 H NMR, FT-IR, UV-Vis spectroscopy, and elemental and lifetime analysis. Interestingly, the lifetimes were 2.31 ms and 2.38 ms for Na[Eu(dipic) 2 $3H 2 O]$4H 2 O in the solid state and in ethanol solution, respectively, though high-frequency vibrations were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In the infrared spectrum of the free dipic ligand, a broad and strong band around 1700 cm -1 and the band at 1330 cm -1 are assigned to C = O and CÀO stretching vibrations of the uncoordinated carboxylate group. Carboxylate bands in free dipic n(C = O) and n(C-O) are transformed into the asymmetric n as (COO), and symmetric n s (COO) stretching vibrations in the complex spectrum and as expected they are shifted after coordination to the metal ion [28,29]. In the complex, the absorption bands due to asymmetric n as and symmetric n s stretching vibrations of the carboxylate group are observed at 1624 cm -1 and 1389 cm -1 , respectively.…”
Section: Sample Characterizationsupporting
confidence: 52%
See 1 more Smart Citation
“…In the infrared spectrum of the free dipic ligand, a broad and strong band around 1700 cm -1 and the band at 1330 cm -1 are assigned to C = O and CÀO stretching vibrations of the uncoordinated carboxylate group. Carboxylate bands in free dipic n(C = O) and n(C-O) are transformed into the asymmetric n as (COO), and symmetric n s (COO) stretching vibrations in the complex spectrum and as expected they are shifted after coordination to the metal ion [28,29]. In the complex, the absorption bands due to asymmetric n as and symmetric n s stretching vibrations of the carboxylate group are observed at 1624 cm -1 and 1389 cm -1 , respectively.…”
Section: Sample Characterizationsupporting
confidence: 52%
“…The electronic spectrum of the complex in 50 : 50 ethanol/aqua solutions (1·10 -5 mol·L -1 ) exhibits absorption bands below 300 nm assignable to intraligand and charge transfer transitions, Figure 2 [29,34].…”
Section: Sample Characterizationmentioning
confidence: 99%
“…The main infrared absorption bands of the complexes and the assignments are listed in Table 1 (see Figure S1 for infrared spectra). All the bands involving carboxyl (–COOH) disappear [ 11 , 15 ], but the asymmetric and symmetric stretching vibration frequencies ( υ as and υ s ) of the carboxylate group (–COO – ) are observed. It is concluded that all the ligands coordinated the terbium ion through their carboxyl.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H-NMR spectrum in Figure S3(a) shows one multiplet (br, 1H) around 8.440 − 8.236 ppm which was assigned to H4 of the pyridine ring. A broad peak at 4.452 ppm (s, 2H) in Figure S3(b) was assigned to H3 and H5 of the pyridine ring, which indicates that the Tb−O and Tb ⟶ N bonds are formed in the complex [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of the process varies with the nature of the ligand and the bonding between the ligand and the lanthanide ion. Polydentate pyridine carboxylates are particularly promising candidates as sensitizers: [5][6][7] the large lanthanide ions act as hard acids and form strong bonds with ligands having O and N donor atoms such that the resultant hybrids usually exhibit not only high thermal stabilities but also intense photoluminescence.…”
mentioning
confidence: 99%